Factors Affecting Personal Bankruptcy among Malaysians - Che-Yahya, Norliza; Mohd Kassim, Nor Akila; Alyasa-Gan, Siti Sarah; Nori, Beche Nediam (Information Management and Business Review, 2023)
Malaysia faces higher bankruptcy cases involving personal bankruptcies among Malaysians despite increasing the threshold of a personal bankruptcy declaration. This research aims to study the factors influencing Malaysian personal bankruptcy, utilizing the macroeconomic aggregates as the determinants, which are inflation rate (IR), unemployment rate (UE), lending interest rate (LR), Gross Domestic Product (GDP) per capita and household final consumption expenditure (HFCE). This study uses a quantitative approach and time series analysis which includes a group of data from 1985 to 2021, i.e., 37 years of observations. The sample series of time frames is sufficient to assess the long-term relationship between the macroeconomic perspectives and personal bankruptcy. The data was analyzed using multiple linear regression analysis. The finding shows a significant negative relationship between Malaysian personal bankruptcy and unemployment rate, lending interest rate and household final consumption expenditure. In contrast, there is an insignificant relationship between Malaysian personal bankruptcy and the inflation rate